The Influence of Islamic Work Ethics and Islamic Leadership on Organizational Commitment and Performance of Government Employees (Study on the Makassar City Cleanliness Task Force) - Idrus, Arifin; bin MD Latip, Azrin; Tenreng, Mariana (CV. Publikasi Indonesia, 2023)
This study aims to confirm the effect of Islamic work ethics and Islamic leadership on organizational commitment and performance of cleaning staff in Makassar City, which is predominantly Muslim, using 274 employees as a sample. The results of the WarpPLS 7.0 analysis provide evidence that Islamic work ethics is partially proven to increase organizational commitment, but Islamic leadership cannot have a significant effect on organizational commitment. Islamic work ethics and Islamic leadership make a real contribution to improving performance. The role of organizational commitment as an intervening variable is proven not to be a strong mediation in explaining the effect of Islamic work ethics and Islamic leadership on the performance of cleaning staff in Makassar City